4th International Symposium of Space Optical Instruments and Applications Delft, The Netherlands, October 16 -18, 2017 (Springer Proceedings in Physics,, 2018)
This book gathers selected and expanded contributions presented at the 4th Symposium on Space Optical Instruments and Applications, which was held in Delft, the Netherlands, on October 16-18, 2017. This conference series is organized by the Sino-Holland Space Optical Instruments Laboratory, a cooperative platform between China and the Netherlands. The symposium focused on key technological problems regarding optical instruments and their applications in a space context. It covered the latest developments, experiments and results on the theory, instrumentation and applications of space optics. The book is split into five main sections: The first covers optical remote sensing system design, the second focuses on advanced optical system design, and the third addresses remote sensor calibration and measurement. Remote sensing data processing and information extraction are then presented, followed by a final section on remote sensing data applications.